Sex differences in primary hypertension - Sandberg Kathryn; Ji Hong (Biology of Sex Differences, 2012)
Abstract Men have higher blood pressure than women through much of life regardless of race and ethnicity. This is a robust and highly conserved sex difference that it is also observed across species including dogs, rats, mice and chickens and it is found in induced, genetic and transgenic animal models of hypertension. Not only do the differences between the ovarian and testicular hormonal milieu contribute to this sexual dimorphism in blood pressure, the sex chromosomes also play a role in and of themselves. This review primarily focuses on epidemiological studies of blood pressure in men and women and experimental models of hypertension in both sexes. Gaps in current knowledge regarding what underlie male-female differences in blood pressure control are discussed. Elucidating the mechanisms underlying sex differences in hypertension may lead to the development of anti-hypertensives tailored to one's sex and ultimately to improved therapeutic strategies for treating this disease and preventing its devastating consequences.